Levers of organization design how managers use accountability systems for greater performance and commitment - Simons, Robert (Boston, Mass. : Harvard Business School Press, 2005)
Annotation THE DESIGN OF AN ORGANIZATION - the accountability system that defines roles, rights, and responsibilities throughout the firm-has a direct impact on the performance of every employee. Yet few leaders devote focused attention to how this design is chosen, implemented, and adjusted over time. Robert Simons argues that by viewing design as a powerful and proactive management lever-rather than an inevitable outcome of corporate evolution-leaders can maximize productivity across every level of the organization. Levers of Organization Design presents a new design theory based on four key yet often underrated categories: customer definition, critical performance variables, creative tension, and commitment to mission. Building from these core areas, Simons lays out a step-by-step process leaders can follow to create structures and accountability systems that positively influence how people do their work, where they focus their attention, and how their activities can be aligned to contribute to overall strategic goals. He also introduces four levers of organization design-unit configuration, diagnostic control systems, interactive networks, and responsibility to others-that leaders can manipulate to vastly improve overall organizational efficiency and effectiveness. For anyone accountable for measuring and managing performance, this book shows how good design can become an organization's roadmap to success.
Annotation.
Title from title screen.
Includes bibliographical references and index.
Keywords: Organizational behavior; Organizational change; Organization; Organization; Organizational behavior; Organizational change; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books